Diagnostic Accuracy of Contrast-Enhanced CT Scan in the Diagnosis of Small Bowel Obstruction: A Validation Study Using Operative Findings as the Gold Standard - Hameed, Najma; Roghani, Inayat Shah (Biological and Clinical Sciences Research Journal, 2025)
Small bowel obstruction (SBO) is a common surgical emergency requiring prompt and accurate diagnosis to prevent complications such as ischemia and perforation. Contrast-enhanced computed tomography (CT) has emerged as a crucial imaging modality for SBO detection. This study evaluates the diagnostic accuracy of contrast-enhanced CT in diagnosing SBO, using operative findings from laparotomy as the gold standard. Objective: To evaluate the diagnostic accuracy of contrast-enhanced computed tomography (CT) in diagnosing small bowel obstruction (SBO), using operative findings from laparotomy as the gold standard. Methodology: This cross-sectional validation study was carried out at the Radiology Department of North West General Hospital, Peshawar from 25-12-2022 to 25-06-2023. One hundred and eighty-four patients aged 18 to 65 years, presenting with clinically suspected SBO, were included. The sample size was calculated using a sensitivity of 76.6%, a specificity of 75%, 16% prevalence, and a 95% confidence level. Contrast-enhanced CT scans were performed using a 16-slice Toshiba scanner, and findings were compared with operative results. We assessed the diagnostic accuracy of contrast-enhanced CT. Results: Out of 194 patients, SBO was detected on CT in 113 (58.2%) cases, with 99 true positives and 14 false positives. Among the 81 patients classified as negative on CT, 12 were false negatives, and 69 were true negatives. CT demonstrated a sensitivity of 89.19%, specificity of 83.1%, PPV of 87.61%, NPV of 85.19%, and diagnostic accuracy of 86.60%. Conclusion: Contrast-enhanced CT is a reliable and accurate diagnostic tool for SBO, with high sensitivity and specificity, making it essential for early diagnosis and management, minimizing complications such as ischemia or perforation.